2021
DOI: 10.1007/s40820-020-00560-9
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-Mediated Synergistic Cancer Therapy: Small Microbiome Has a Big Hope

Abstract: The use of bacteria to specifically migrate to cancerous tissue and elicit an antitumor immune response provides a promising platform against cancer with significantly high potency. With dozens of clinical trials underway, some researchers hold the following views: “humans are nearing the first commercial live bacteria therapeutic.” However, the facultative anaerobe Salmonella typhimurium VNP20009, which is particularly safe and shows anticancer effects in preclinical studies, had failed in a phase I clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 101 publications
0
49
0
Order By: Relevance
“…Firstly, due to their potential to cause infections in patients, live microbes may cause the immune system to attack healthy cells, and their use may be in company with the risk of deadly infection. In addition, the facultative anaerobe Salmonella typhimurium VNP20009 failed in a phase I clinical trial because the monotherapy was found not enough to eliminate tumor effectively 20 . Microbe-based cancer immunotherapy is still in its early stage 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, due to their potential to cause infections in patients, live microbes may cause the immune system to attack healthy cells, and their use may be in company with the risk of deadly infection. In addition, the facultative anaerobe Salmonella typhimurium VNP20009 failed in a phase I clinical trial because the monotherapy was found not enough to eliminate tumor effectively 20 . Microbe-based cancer immunotherapy is still in its early stage 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Although bacteria-mediated tumor therapy could be recognized as the oldest type of cancer immunotherapy, its proper clinical application still needs to fulfill very strict requirements of safety and efficacy in both mechanistic and large scale (pre-)clinical studies ( 8 , 54 ). Early bacteria-based antitumor drug like Coley’s toxin was made of natural pathogen, which showed clear efficacy against multiple types of tumor but suffered from toxicity ( 4 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly Two decades ago, the attenuated salmonella VNP20009 was approved to enter a phase I clinical trial, in which its safety was clearly proved but efficacy was insignificant ( 55 ). These days, the emerging synthetic biology technology provided more possibilities for engineering both safe and efficient antitumor bacteria, and combining the synthetic bacteria with other tumor killing agents ( 13 , 15 , 54 , 56 , 57 ). These advances together shed a light on the future of understanding and applying the bacteria-mediated tumor therapy clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, more bacterial species, including Bifidobacterium spp., Clostridium spp., S. typhimurium, and E. coli, have been found to accumulate in tumor sites [25]. In light of their inherent capacities of breaking related biological barriers and colonizing tumor tissue, these bacterial species have been intensively attracted for cancer therapy [107,108]. Moreover, equipped with technologies progressed rapidly in gene editing and bio-interface science, bacteria have been engineered to act as vehicles for the delivery of therapeutic agents including both small molecules and biomacromolecules (proteins and DNAs) (Table 2) [20,54,64,100,109].…”
Section: Cancersmentioning
confidence: 99%